1995
DOI: 10.1007/bf00618487
|View full text |Cite
|
Sign up to set email alerts
|

A dynamometer for evaluation of dynamic muscle work

Abstract: The validation of a new dynamometer for evaluation of dynamic muscle work is presented. The device was based on a precise measurement of load displacements of any machine using gravitational loads as external resistance. It allowed, through a sensor consisting of an infrared photo interrupter, the calculation of velocity, force and power during concentric, eccentric and stretch-shortening cycle activity. To validate the dynamometer 33 male and female track and field athletes (12 throwers and 21 jumpers) partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
152
1
30

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(195 citation statements)
references
References 19 publications
12
152
1
30
Order By: Relevance
“…The findings of this study are similar to those reported by Bosco et al 8 , and Hori et al 9 who found strong and moderate inverse relationships of r = -0.93 (p<0.01) between 30 m and CMJ and r = -0.69 (p<0.01) between 20 m and CMJ performances, respectively. The correlations in this study are not as strong as those reported by Bosco et al 8 although the subjects used in the earlier study were a mixed group of male and female jump athletes which may have increased the range of values attained.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of this study are similar to those reported by Bosco et al 8 , and Hori et al 9 who found strong and moderate inverse relationships of r = -0.93 (p<0.01) between 30 m and CMJ and r = -0.69 (p<0.01) between 20 m and CMJ performances, respectively. The correlations in this study are not as strong as those reported by Bosco et al 8 although the subjects used in the earlier study were a mixed group of male and female jump athletes which may have increased the range of values attained.…”
Section: Discussionsupporting
confidence: 92%
“…The correlations in this study are not as strong as those reported by Bosco et al 8 although the subjects used in the earlier study were a mixed group of male and female jump athletes which may have increased the range of values attained. Hori et al 9 used subjects with similar age and anthropometric characteristics to the present study, with the mean values for 20 m sprint time and CMJ height (3.17 s and 41.5 cm) similar to those reported in the present study (3.05 s and 42.8 cm).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The explosive strength of the lower limbs of the handball players was indirectly measured through the vertical jump test on a resistive table connected to a digital timer, following protocol proposed by Bosco et al (11) .…”
Section: Vertical Jump Testmentioning
confidence: 99%
“…In order to give an experimental measure of these forces, Bosco et al [15] proposed a validation of a new dynamometer for the evaluation of dynamic muscle work.…”
Section: Introductionmentioning
confidence: 99%